Value of unenhanced CT combined with clinical features in predicting adnexal torsion in women - Xiaowen GU; Lu JIANG; Lei CUI; Xiaoxia WU; Jibin ZHANG; Ying FEI (Zhongguo Linchuang Yixue)
ObjectiveTo investigate the value of unenhanced CT combined with clinical features in predicting adnexal torsion in women with abdominal pain and an adnexal mass. MethodsA retrospective selection of patients with abdominal pain and an adnexal mass underwent operation in 2 tertiary hospitals from January 2018 to September 2023. The torsion group (n＝53) and non-torsion group (n＝53) were matched in a 1∶1 ratio. 15 CT signs of adnexal masses were reviewed independently by two radiologists using a double-blind method. The high-risk factors were screened using multivariate logistic regression analysis. The diagnostic values of high-risk factors for adnexal torsion were assessed using receiver operating characteristic (ROC) curves.ResultsAccording to the surgical and pathological results, the most common adnexal mass in torsion group was mature cystic teratoma (32.1%), and the most common mass in the non-torsion group was adnexal abscess (20.8%). The age, fever rate, white blood cell count, location of mass, thickened fallopian tube rate, and pelvic effusion rate were not statistically different between the two groups, the nausea and vomiting and remaining CT signs were significant different between the two groups (P＜0.05). Multivariate logistic analysis showed that nausea and vomiting (OR＝4.886), navel sign (OR＝22.733), and whirl sign (OR＝43.462) were independently associated with adnexal torsion (P＜0.05). The area under the curve (AUC) of nausea and vomiting, navel sign, and whirl sign were 0.717, 0.802, and 0.840, respectively; AUC of the combination of all three was 0.877 with 92.45% of sensitivity, 84.91% of specificity, 85.96% of positive predictive value, 91.84% of negative predictive value, and 88.68% of accuracy. ConclusionsFor women with abdominal pain and an adnexal mass, nausea and vomiting, navel sign, and whirl sign are help of predicting adnexal torsion, and combination value of all three is best.